Seismic assessment of framed buildings: a pseudo-adaptive uncoupled modal response analysis - Jerez Barbosa, Sandra Rocio; Mebarki, Ahmed (Taylor & Francis Group, 2011)
The Pseudo-Adaptive Uncoupled Modal Response Analysis proposed herein aims to estimate the seismic response of structures. In comparison to complete nonlinear time history analysis, the proposed method provides an acceptable accuracy with a reduced calculation time duration. It relies on the energy based approach to build the capacity curve and a pseudo-adaptive feature that considers changes in modal shapes after yielding. Low- and medium-rise reinforced concrete buildings are tested. The numerical results are in good accordance with the results obtained by a complete time history analysis. They are also compared to other existing methods and with available experimental measures.
Keywords: Earthquake Engineering; Seismic Assessment; Pushover Analysis